2021
DOI: 10.1523/eneuro.0314-21.2021
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Effects of Transplanted Human Bone Marrow Endothelial Progenitors on Functional and Cellular Components of Blood-Spinal Cord Barrier in ALS Mice

Abstract: Convincing evidence of blood-spinal cord barrier (BSCB) alterations has been demonstrated in amyotrophic lateral sclerosis (ALS) and barrier repair is imperative to prevent motor neuron dysfunction.We showed benefits of human bone marrow-derived CD34+ cells (hBM34+) and endothelial progenitor cells (hBM-EPCs) intravenous transplantation into symptomatic G93A SOD1 mutant mice on barrier reparative processes. These gains likely occurred by replacement of damaged endothelial cells, prolonging motor neuron surviva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 68 publications
(105 reference statements)
0
6
0
Order By: Relevance
“…Repair of the BCNSB pathology in ALS via stem cell transplantation has provided some evidence of symptomatic improvement in SOD1 G93A mice. The intravenous transplantation of human bone marrow-derived CD34+ cells (hBM34+) and endothelial progenitor cells (hBM-EPCs) enhanced the replacement of damaged endothelial cells in the CNS capillaries (Garbuzova-Davis et al, 2017 , 2018 , 2019 , 2021 ; Eve et al, 2018 ). One mechanism of hBM-EPCs on the endothelium includes excretion of extracellular vesicles that transfer biomolecules to facilitate the repair of damaged microvascular endothelium in ALS (Garbuzova-Davis et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Repair of the BCNSB pathology in ALS via stem cell transplantation has provided some evidence of symptomatic improvement in SOD1 G93A mice. The intravenous transplantation of human bone marrow-derived CD34+ cells (hBM34+) and endothelial progenitor cells (hBM-EPCs) enhanced the replacement of damaged endothelial cells in the CNS capillaries (Garbuzova-Davis et al, 2017 , 2018 , 2019 , 2021 ; Eve et al, 2018 ). One mechanism of hBM-EPCs on the endothelium includes excretion of extracellular vesicles that transfer biomolecules to facilitate the repair of damaged microvascular endothelium in ALS (Garbuzova-Davis et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…One mechanism of hBM-EPCs on the endothelium includes excretion of extracellular vesicles that transfer biomolecules to facilitate the repair of damaged microvascular endothelium in ALS (Garbuzova-Davis et al, 2020 ). Additionally, mice receiving hBM-EPCs have increased tight junction protein levels, capillary pericyte coverage, and basement membrane laminin expression, all of which maintain capillary endothelium integrity (Garbuzova-Davis et al, 2021 ). Ultimately, these mechanisms may prevent the entry of immune or inflammatory mediators which can contribute to motor neuron dysfunction (Garbuzova-Davis et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…However, the impacts of cell transplantation on the integrity of the endothelium in murine CNS capillaries were not fully established. In a study by Garbuzova-Davis et al [ 53 ], functional and cellular constituents of the microvascular endothelium in the spinal cord were evaluated after the administration of hBM34 + cells and hBMEPCs, at the same dose of 1 × 10 6 cells, into G93A SOD1 mice. The findings showed that ALS mice receiving hBMEPC vs. hBM34 + cell treatment significantly increased the levels of TJ claudin-5, occludin, and ZO-1 proteins; enhanced the coverage of capillary pericytes; amended immunoexpression of basement membrane laminin; and increased expression of endothelial cytoskeletal F-actin.…”
Section: Cellular Approach To B-cns-b Repairmentioning
confidence: 99%
“…Furthermore, a loss of pericytes in the choroid plexus has been detected in patients with ALS, coupled with a deregulation of the blood-cerebrospinal fluid (CSF) barrier [132]. In a murine model of ALS, reduced pericyte coverage in spinal cord capillaries has also been demonstrated [133]. Interestingly, the administration of adipose-derived pericytes has shown promising results in ALS mice, extending their survival and increasing antioxidant enzymes in the brain [134].…”
Section: Pericyte Loss In Amyotrophic Lateral Sclerosis (Als)mentioning
confidence: 99%